A study of the translation of the Mahayana Buddhist Sutra by Sathien Bodinanda A case study of the Vajraprajñāpāramitā Sūtra - Mahatharathong, Wannarat (Mahachula Academic Journal, 2023)
The purpose of this research article is to study the style translation of the translation of the Mahayana Buddhist Sutra "The Vajraprajñāpāramitā Sūtra" from the Chinese original into the Thai language of Sathien Bodhinanda by means of a comparative study of the text with the Chinese manuscript. Focus on the difference from the original and analyze the cause of the difference. The results showed that the translation of Sathian had a modification of the composition style. Fill in the text and find a mistranslation. The adaptation of the style of writing and the addition of that It is because of the principle of using the language of the destination language and to expand it to the audience. As for translation errors, they are mainly due to lack of reviewers or due to typographical errors.